2016
DOI: 10.1515/oszn-2016-0006
|View full text |Cite
|
Sign up to set email alerts
|

Selected properties of cobalt-contaminated soil following the application of neutralising substances

Abstract: The aim of the study was to determine the influence of increasing cobalt soil contamination (0 mg·kg−1, 20 mg·kg−1, 40 mg·kg−1, 80 mg·kg−1, 160 mg·kg−1, 320 mg·kg−1) after the application of neutralising substances on selected soil properties. In the soil without an addition of neutralising substances, the highest doses of cobalt caused the pH, total exchangeable bases, cation exchange capacity and the degree of base saturation to decrease and the hydrolytic acidity of soil to increase. Among the substances us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…The lesser harmfulness of cobalt occurring in alkaline or neutral soil environment is also confirmed in the study by Wendling et al [2009]. A favourable effect of calcium oxide on the soil properties analysed in the work was also found by Kosiorek and Wyszkowski [2016], and Wyszkowski and Sivitskaya [2015]. The study by Azeez and Van-Averbeke [2012] confirmed the positive effect of farmyard manure on physico-chemical soil properties, particularly on the soil pH.…”
Section: Resultssupporting
confidence: 76%
“…The lesser harmfulness of cobalt occurring in alkaline or neutral soil environment is also confirmed in the study by Wendling et al [2009]. A favourable effect of calcium oxide on the soil properties analysed in the work was also found by Kosiorek and Wyszkowski [2016], and Wyszkowski and Sivitskaya [2015]. The study by Azeez and Van-Averbeke [2012] confirmed the positive effect of farmyard manure on physico-chemical soil properties, particularly on the soil pH.…”
Section: Resultssupporting
confidence: 76%
“…The strongest effect on the uptake of this element is attributed to the plant’s species, age and mechanisms which occur in the plant. A significant role is also played by soil properties and climatic conditions characteristic for a given territory (Kashin 2011; Kosiorek and Wyszkowski 2016a, b). It is therefore essential to search for optimal methods to limit cobalt uptake by plants, for example through application of different substances to soil and by using phytoremediation abilities of plants (Pszczółkowski et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In other research by Kosiorek and Wyszkowski (2016b), the most beneficial effect on soil properties was that of zeolite and calcium oxide. They caused an increase in soil pH, total exchangeable bases, cation exchange capacity, and a decrease in hydrolytic acidity.…”
Section: Resultsmentioning
confidence: 72%